ANALISIS DU PONT SYSTEM DALAM MENGUKUR KINERJA KEUANGAN PADA PT. UNITED TRACTORS TBK PEKANBARU - Suci Rahmadani; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT The purpose of the research conducted at PT United Tractors Tbk Pekanbaru is to evaluate financial performance from 2017 to 2021 using the du pont system analysis method which calculates the activity ratio and profitability ratio. The secondary data used in this study were taken from the financial statements of PT United Tractors Tbk Pekanbaru from 2017 to 2021. The data collection technique used is the documentation method. The indicators in this study are the ratio of total asset turnover (TATO), net profit margin (NPM), return on investment (ROI), and return on equity (ROE). The results of the study explain that the financial performance of PT United Tractors Tbk Pekanbaru is said to be less good because the profitability ratio consisting of net profit margin, return on investment, and return on equity has not been able to meet the applicable measurement standards during the five-year period, only the activity ratio, namely total asset turnover, which reaches the measurement requirements but still fluctuates. This is due to the low net profit generated by the company and the unstable sales and total assets of the company. Keywords: Du Pont System, Financial Performance